The Regulation of Glutamate Transporter 1 in the Rapid Antidepressant-Like Effect of Ketamine in Mice - Chen, Yaping; Shen, Mengxin; Liu, Xu; Xu, Jiangping; Wang, Chuang (Frontiers in Behavioral Neuroscience, 2022)
Accumulating evidence suggests that glutamate clearance plays a critical role in the pathophysiology and treatment of depression. Preclinical and clinical studies have demonstrated that ketamine provides an immediate and sustained antidepressant effect. However, the precise mechanism of its action remains to be elucidated. Glutamate transporter 1 (GLT1) participates in glutamate clearance; therefore, we hypothesized that GLT1 may play an important role in the antidepressant effect of ketamine. In this study, we determined that GLT1 inhibition blocks the antidepressant-like properties of ketamine and alters the phosphorylation of the mammalian target of rapamycin (mTOR) in the prefrontal cortex (PFC). Our results show that pretreatment with dihydrokainic acid (DHK), a GLT1 inhibitor, alleviated the antidepressant-like effect of ketamine, and decreased the level of phosphorylated mTOR (pmTOR) in mice (which is normally upregulated by ketamine). In addition, inhibition of α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor and L-type voltage-dependent calcium channel (L-VDCC) significantly abolished the antidepressant-like effect of ketamine. Moreover, inhibition of L-VDCC significantly blocked the upregulation of GLT1 and BDNF in the PFC of mice. The inhibition of the AMPA receptor only significantly alleviated BDNF. Our results provide insight into the role of GLT1 as the critical presynaptic molecule participating in the pathophysiological mechanism of depression and contributing to the antidepressant-like effect of ketamine. In addition, our study confirms that both AMPA receptor and L-VDCC are crucial factors in the immediate antidepressant-like effect of ketamine.